UMPSA celebrates 14 hajj pilgrims - Mohd Mukhris, Awang (UMPSA, 2024)
KUANTAN, 8 May 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) celebrated 14 UMPSA staff members who will perform hajj this year.